An investigation into the pretreating of a low-grade bauxite ore using magnetic separation and flotation processes (Rudarsko-geološko-naftni zbornik, 2025)
A bauxite reserve with an Al2O3 grade less than 50% is classified as low-grade bauxite due to the presence of impurities such as silica and iron oxide, thus pretreatment before concentration (Bayer process) is required to reduce SiO2 and Fe2O3. Hence, this study investigates the feasibility of removing SiO2 and Fe2O3 from a low-grade bauxite ore using magnetic separation and flotation processes. Different magnetic methods were utilized to eliminate iron impurities, and the results indicated that the high-gradient magnetic separation (HGMS) with an intensity of 18000 Gauss had the best output in reducing Fe2O3 with 18.03% Fe2O3 content and a 31.15% removal rate. In the next step, reverse and direct flotation techniques were employed to remove silica from the sample. The findings showed that the highest removal efficiency of SiO2 was achieved using the reverse flotation process at 750 g/t Armac C collector, 1200 g/t starch, 40 g/t MIBC and 11 pulp pH. Ultimately, the HGMS followed by reverse flotation with an Armac C collector (750 g/t) was implemented on the bauxite sample, and the content of Fe2O3, and SiO2, silica removal efficiency, and Al2O3/SiO2 mass ratio was found to be 17.76, and 22.11%, 45.22% and 1.63, respectively, indicating that HGMS followed by flotation is not effective enough in reducing iron oxide and silica, and therefore requires further pretreatment and/or the study of a suitable alternative method. The behaviour observed may be because iron oxide and silica minerals were fine-grained diseminated in the bauxite sample.